Teacher's Reinforcement in Teaching English at High School Level - Dian Frahesti; Harum Natasha (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2020)
This study aims to determine the teacher's reinforcement in teaching English at the high school level. This is important to do because strengthening is one of the strategies that teachers can apply in increasing interest and motivation to learn to achieve satisfactory student achievement. This research uses qualitative methods with descriptive techniques. In data collection, researchers conducted interviews and observations on teachers of SMA Islam Negeri 2 Kuantan Singingi to determine the components of reinforcement used by teachers in learning English. The results of this study indicate that the English teacher uses verbal and non-verbal reinforcement in learning English. For verbal reinforcement, the teacher uses reinforcement with words and reinforcement with sentences. For non-verbal reinforcement, the teacher uses gesture reinforcement, closeness strengthening, contact strengthening, activity reinforcement, and token reinforcement. The reinforcement most often used by teachers in teaching English was reinforcement with words, while the reinforcement that was rarely used by teachers was token reinforcement.